How does the increase in foreign players affect football? - Sever, O.; Cigerci, E.; Öztop, M.; Ipekoglu, G.; Gönülates, S.; Akyildiz, Z.; Nobari, H. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background In the study, we tried to analyze the effects of foreign players on Turkish Super League matches. For this purpose, in this long-term study, 1836 competition data played in 6 seasons between 2014 and 2020 was obtained from www.mackolik.com each year.